COVID-19 surveillance in wastewater: An epidemiological tool for the monitoring of SARS-CoV-2 - Maryam, Sajida; Ul Haq, Ihtisham; Yahya, Galal; Ul Haq, Mehboob; Algammal, Abdelazeem M.; Saber, Sameh; Cavalu, Simona (Frontiers in Cellular and Infection Microbiology, 2023)
COVID-19 pandemic caused immense inquisitiveness globally to know about the range of information about the virus’s possible routes of transmission, diagnostics, and therapeutic tools. Worldwide studies pointed out the monitoring and early surveillance techniques based on the identification of viral RNA in wastewater. They indicated the presence of the SARC-CoV-2 RNA in human feces. It is shed via excreta including mucus, feces, saliva, and sputum. Subsequently, they get dumped into wastewater and their presence in wastewater provides a chance to use it as a tool to prevent and eradicate the virus. The monitoring of it is still ongoing in many regions of the world as a tool for “Warning signal” yet, many limitations of the wastewater surveillance had also been identified.